PERLINDUNGAN HUKUM TERHADAP SELLER SHOPEE DALAM SISTEM PEMBAYARAN CASH ON DELIVERY (COD) - Asmi, Nurul; Marilang; Istiqamah; Kahpi, Ashabul (Alauddin Law Development Journal (ALDEV), 2025)
Business actors in advancing their business, each e-commerce company must be able to compete in improving its services, one of which is in terms of cash on delivery (COD) payment methods. The use of the COD method in e-commerce is increasingly in demand because in addition to being easier, it also offers various benefits for consumers. However, it is also possible to cause problems, such as consumers who do not have good intentions in terms of payments. For this reason, business actors are also entitled to protection if their rights are ignored. So the parties involved must pay attention to what their rights and obligations are so that no party feels aggrieved. The responsibilities that arise in online buying and selling transactions using the COD method on shopee are born based on the legal relationship of the parties.